The Impact of Western Sanctions Imposed on the Russian Federation on German Trade : Prediction vs. Reality - Losos, Vojtěch (2025)
This bachelor’s thesis examines the impact of Western sanctions imposed on the Russian Federation on German trade patterns following the 2022 invasion using two separate analytical approaches. The first presents counterfactual scenarios for import and export flows using ARIMA models and bilateral trade data from the Eurostat Comext database. These projections demonstrate how imports and exports might have developed in the absence of the conflict and the sanctions linked to it. The second analysis compares actual developments with forecasts from various institutions – specifically the International Monetary Fund, European Commission, and the ifo Institute – and evaluates their accuracy using Mean Actual Forecast Error and Mean Bias. The results of the initial analysis reveal a structural shift in the bilateral trade relationship between Germany and Russia, with a notable shortfall in both exports and imports relative to the counterfactual scenario. The institutional comparison shows that the forecasts recognised the geopolitical shock but failed to assess its scale and duration. These findings contribute to a better understanding of how large geopolitical disruptions affect trade and highlight the limitations of conventional institutional forecasting approaches.